The Interplay Between Thyroid Dysfunction and Kidney Disease - Narasaki, Yoko; Sohn, Peter; Rhee, Connie M (Seminars in nephrology, 2021)
Hypothyroidism is a highly prevalent endocrine complication in chronic kidney disease (CKD) patients. A large body of evidence has shown that there is a bidirectional relationship between thyroid dysfunction and kidney disease, yet there are many remaining gaps in knowledge in regards to the clinical management of CKD patients with hypothyroidism, including those receiving hemodialysis and peritoneal dialysis. Given that hypothyroidism has been associated with many deleterious outcomes including a higher risk of (1) mortality, (2) cardiovascular disease, (3) impaired health-related quality of life, and (4) altered body composition in both non-CKD and CKD patients, future research is needed to establish the appropriate screening, diagnosis, and treatment approaches in these populations.